Experimental Research and Numerical Simulation on Gas-Liquid Separation Performance at High Gas Void Fraction of Helically Coiled Tube Separator - Yongxue Zhang; Chan Guo; Hucan Hou; Guomin Xue (International Journal of Chemical Engineering)
The industrial removal process of the light hydrocarbon and water from wet natural gas can be simulated in laboratory with the independently designed helically coiled tube gas-liquid separator. Experiment and numerical simulation are combined to analyze the influences of various inlet velocities and gas void fractions on the gas-liquid separation efficiency and pressure-drop between the inlet and outlet of the helically coiled tube. The results show that, at the inlet velocity of 4 m/s to 18 m/s and the gas void fraction of 88% to 97% for the gas-liquid mixture, the gas-liquid separation efficiency increases at the beginning and then decreases with increasing inlet velocity. Afterwards there is another increasing trend again. The gradient of pressure-drop increases slowly and then fast with the increasing inlet velocity. On the other hand, the gas-liquid separation efficiency first increases with the gas void fraction and then shows a decreasing trend while the pressure-drop keeps falling down with the gas void fraction increasing. Above all the optimal operating parameters of the helically coiled tube separator are inlet velocity of 13 m/s and gas void fraction of 93%, and the separation efficiency and pressure-drop are 95.2% and 0.3 MPa, respectively.